2007
DOI: 10.1080/14767050701434747
|View full text |Cite
|
Sign up to set email alerts
|

Doppler study of the embryonic heart in normal pregnant women

Abstract: Doppler examination of the fetal cardiac function is possible after 5 weeks of gestation. After 8 weeks of gestation, the fetal heart is morphologically mature but has not yet achieved effective myocardial compliance. The embryonic human heart is dependent on the atrial contraction for ventricular filling throughout the period of cardiac development. Non-survivors manifest myocardial dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 19 publications
5
38
0
Order By: Relevance
“…9 Although the MPI has been assessed by many authors in the second and third trimesters, there is a paucity of data on the MPI in early pregnancy. 2 Assessment of fetal cardiac function has a role in determining normal physiologic characteristics and underlying pathophysiologic characteristics of fetal conditions. It may have a role in the first trimester in identifying fetuses at an increased risk of miscarriage, prediction of cardiac defects in fetuses with increased nuchal translucency, and also in early detection of the development of twin-to-twin transfusion syndrome in monochorionic twins.…”
Section: Abbreviationsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Although the MPI has been assessed by many authors in the second and third trimesters, there is a paucity of data on the MPI in early pregnancy. 2 Assessment of fetal cardiac function has a role in determining normal physiologic characteristics and underlying pathophysiologic characteristics of fetal conditions. It may have a role in the first trimester in identifying fetuses at an increased risk of miscarriage, prediction of cardiac defects in fetuses with increased nuchal translucency, and also in early detection of the development of twin-to-twin transfusion syndrome in monochorionic twins.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Those studies found that the proportion of the cardiac cycle occupied by both the isovolumetric relaxation time (IVRT) and isovolumetric contraction time (ICT) reduces during the first trimester. [2][3][4] The myocardial performance index (MPI) is a useful noninvasive Doppler-derived method of evaluating combined systolic and diastolic function, first described in …”
mentioning
confidence: 99%
“…It should be noted that it is technically extremely difficult to obtain these tracings and, thus, very prolonged dwell times may be necessary. Some have described performing a measurement of the heart diameter, heart rate and inflow and outflow waveforms "after 5 weeks" [138]. No details are available on exposure levels.…”
Section: Is Doppler Different and Can It Have Detrimental Effects On mentioning
confidence: 99%
“…Serial observations from the first and early second trimesters will provide further insight into the evolution of fetal cardiovascular disease during this period of very rapid fetal cardiovascular and general somatic growth. Already underway, first-trimester observations of fetal heart function may help us better to understand the role of myocardial function in the viability of pregnancies [85,86] In addition to first-trimester fetal echocardiography, the development of high resolution 3D and 4D fetal echocardiography will likely revolutionize prenatal detection through a reduction in scanning time, decrease in operator and window dependence, improved comprehension of the pathology and more accurate volumetric data [87].…”
Section: Evolving and Future Directions In Fetal Echocardiographymentioning
confidence: 99%